Buy Me the Sky : The Remarkable Truth of China's One-Child GenerationsXinran - Xinran, 1958-; Translated by Dobson, David, 1940- and Tyldesley, Esther (London Rider & Co., 2016)
Tells the remarkable stories of men and women born in China after 1979 - the recent generations raised under China's single-child policy. From the businessman's son unable to pack his own suitcase, to the PhD student who pulled herself out of extreme rural poverty, this book shows how these generations embody the hopes and fears of a great nation
Include Appendix
Keywords: Only child -- China -- Generation Y